2016
DOI: 10.1088/0029-5515/56/4/046014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plasma response on the fast ion losses due to ELM control coils in ITER

Abstract: Mitigating edge localized modes (ELMs) with resonant magnetic perturbations (RMPs) can increase energetic particle losses and resulting wall loads, which have previously been studied in the vacuum approximation. This paper presents recent results of fusion alpha and NBI ion losses in the ITER baseline scenario modelled with the Monte Carlo orbit following code ASCOT in a realistic magnetic field including the effect of the plasma response. The response was found to reduce alpha particle losses but increase NBI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 18 publications
1
61
0
Order By: Relevance
“…[32]. Some of these response field data have been used for further investigation of the fast ion losses in ITER [5].…”
Section: Plasma Response For Four Iter Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…[32]. Some of these response field data have been used for further investigation of the fast ion losses in ITER [5].…”
Section: Plasma Response For Four Iter Scenariosmentioning
confidence: 99%
“…However, as has been recently realized, taking into account the plasma response to the 3D external fields may be crucial. This is useful not only just for understanding the modification (plasma shielding and/or amplification) of the field structure due to the plasma response, but also, and perhaps even more importantly, for providing better guidance of correcting these field errors, for understanding the potential mode locking induced by the low-n components of these fields, and for further investigation of energetic particle losses in the presence of the total 3D field perturbations including the plasma response [5].…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Finally, the computed plasma response field can be valuable input data for further studies, such as the (enhanced) energetic particle losses due to 3D RMP fields, and the resulting divertor-wall heat loads. 24 This study has revealed that there are essentially two types of plasma response to the applied RMP fields: One is the so-called core-kink response and the other is the edgepeeling response. 7 The difference is that the plasma displacement is strongly localised near the plasma edge-in the pedestal region-with the edge-peeling type of response and is often associated with a dominant single poloidal harmonics in terms of the radial plasma displacement.…”
Section: Introductionmentioning
confidence: 99%
“…ASCOT has recently been applied to extensive studies of fusion α-particle wall loads in various ITER scenarios [91,92] with three-dimensional magnetic background and first wall. The effects of toroidal field ripple, mitigated by ferritic inserts at the toroidal field coils, as well as non-periodic magnetic field perturbations caused by the ferritic test blanket modules and control coils for edge-localized modes were studied.…”
Section: Reconstruction Of Ascot Simulations Based On Grs and Ctsmentioning
confidence: 99%